QoS assurance for PON-based fronthaul and backhaul systems of 5G cloud radio access networks. (7th May 2021) - Waqar, Muhammad; Kim, Ajung
The newly proposed fronthaul and backhaul (FB) segments in the cloud-radio access networks (C-RANs) could be leveraging solutions to satisfy the 5G demands, but the rigorous one-way delay and packet delay variations (PDVs) requirements of fronthaul networks are the bottleneck. Time division multiplexing (TDM)-based passive optical networks (PONs) can be a promising candidate to carry the fronthaul traffic, but the TDM-PON systems have limitations to meet the fronthaul QoS requirements due to unavoidable delays at the switching nodes. Moreover, the unification of FB traffics over the same segment is vital to fully exploit the cost benefits, but due to the poor performance of the PON systems for the fronthaul traffic, the backhaul traffic could not be forwarded through the same fronthaul segments. Therefore, in this paper, we propose and implemented the strict priority and frame pre-emption-based buffering schemes to transport the FB packet flows simultaneously at tolerable delays and PDVs.